2010
DOI: 10.1093/nar/gkq194
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the FoxM1 DNA-recognition domain bound to a promoter sequence

Abstract: FoxM1 is a member of the Forkhead family of transcription factors and is implicated in inducing cell proliferation and some forms of tumorigenesis. It binds promoter regions with a preference for tandem repeats of a consensus ‘TAAACA’ recognition sequence. The affinity of the isolated FoxM1 DNA-binding domain for this site is in the micromolar range, lower than observed for other Forkhead proteins. To explain these FoxM1 features, we determined the crystal structure of its DNA-binding domain in complex with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 46 publications
6
109
0
Order By: Relevance
“…Its forkhead DNA-binding domain (FHD) shares only 18% sequence identity with that of FoxA1, and FoxM1 has lower affinity for the forkhead consensus binding site than other Fox proteins (Littler et al, 2010). Some investigators have shown that, instead of directly interacting with the DNA of its proliferative targets, FoxM1 attaches to proteins in the DREAM complex -a larger conglomeration of proteins that prevents the transcription of proliferative targets in the quiescent state, but promotes expression of the same targets during the cell cycle (Chen et al, 2013).…”
Section: An Overview Of Fox Transcription Factorsmentioning
confidence: 99%
“…Its forkhead DNA-binding domain (FHD) shares only 18% sequence identity with that of FoxA1, and FoxM1 has lower affinity for the forkhead consensus binding site than other Fox proteins (Littler et al, 2010). Some investigators have shown that, instead of directly interacting with the DNA of its proliferative targets, FoxM1 attaches to proteins in the DREAM complex -a larger conglomeration of proteins that prevents the transcription of proliferative targets in the quiescent state, but promotes expression of the same targets during the cell cycle (Chen et al, 2013).…”
Section: An Overview Of Fox Transcription Factorsmentioning
confidence: 99%
“…To this end, we first simulated ideal B-DNA structures containing the dimer motifs from Figure 6 using the w3DNA server (http://w3dna.rutgers.edu/). Next, we downloaded structural models from the Protein Data Bank (PDB) (Berman et al 2000) containing androgen receptor (Shaffer et al 2004) and FOX (Littler et al 2010) DNA-binding domains (PDB identifiers 1R4I and 3G73) when bound to DNA sequences that closely match the consensus of our composite motifs. Unfortunately, we found no PDB entries with reasonable sequence similarity to NFI.…”
Section: Predicted Cooperative Interactions Are Rigid and Compactmentioning
confidence: 99%
“…The lack of B-Myb binding to promoters in the absence of LIN54 and vice versa is suggestive of cooperativity that is likely dependent on both B-Myb and CHR consensus sites on promoters. In the case of FoxM1, its winged-helix domain has been reported to have a surprisingly low affinity for the consensus element TAAACA (Littler et al 2010). It is plausible that MuvB binding to its consensus sequence and to FoxM1 increases the specific affinity of FoxM1 for the late cell cycle promoters, thereby serving an essential role in recruitment of FoxM1 to the late cell cycle promoters.…”
mentioning
confidence: 99%